Natural latex leather and preparation process thereof
Through the three-layer coating formula and gradient temperature vulcanization process, the slow vulcanization speed and surface problems in the preparation of traditional natural latex leather are solved, and the mechanical properties and durability of the leather are improved, and better functionality and weather resistance are achieved.
Patent Information
- Application Number
- CN202411095685.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2024-12-27
AI Technical Summary
The traditional natural latex leather preparation process has problems such as slow vulcanization speed, easy blister breakage on the second layer, easy cracking on the surface of the product, impermissible aging resistance and unclear transfer patterns.
The three-layer coating formula and gradient temperature vulcanization process are adopted. The first layer of coating contains natural latex, sulfur powder, vulcanization additives, zinc oxide, anti-aging agents and color paste. The second layer of coating contains natural latex, sulfur powder, foaming agent, Thickener, zinc oxide and filler, the third layer of coating contains natural latex, polyurethane, sulfur powder, vulcanization additives, zinc oxide, anti-aging agent, peroxide and polyhydroxy reinforcement materials, and forms a network structure through gradient temperature vulcanization. Enhance the mechanical properties and stability of the leather.
Improves the tensile strength, elongation, tear strength, UV resistance, wear resistance, breathability, waterproofness and the clarity of the surface transfer patterns of the leather, extends the service life of the product, improves functionality and durability sex.
Smart Images

Figure BDA0004987853650000071 
Figure BDA0004987853650000081 
Figure BDA0004987853650000091
Abstract
Description
Technical Field
[0001] The invention relates to the field of natural latex processing, in particular to natural latex leather and a preparation process thereof. Background Art
[0002] Natural rubber refers to a polymer material naturally synthesized by the Hevea brasiliensis tree. It is divided into natural rubber raw rubber and concentrated natural latex according to process requirements. The natural latex collected directly from the rubber tree is called fresh latex, which is a natural macromolecular emulsion formed by rubber particles dispersed in the water phase (i.e. whey). With the difference in rubber tree strains and ages, as well as changes in planting environmental factors such as seasons and climate, the total solid content of fresh natural latex varies greatly, generally between 20% and 45%. Through processes such as centrifugal concentration, the total solid content of fresh natural latex is increased, and the resulting natural latex is called centrifugal concentrated natural latex.
[0003] Traditional processes mainly use polyurethane to prepare leather. However, water-based polyurethane is expensive and is a non-renewable petrochemical raw material. In comparison, natural latex is cheap and a renewable resource. However, the existing process of using natural latex to directly make leather has the following problems: (1) slow vulcanization speed; (2) the second foaming layer is prone to bubble breakage; (3) the surface of the product is prone to cracking, is not resistant to aging, and the transfer pattern is unclear. Research to overcome the above defects is of great significance to the development of the natural rubber industry. Summary of the invention
[0004] In view of this, the present invention provides a natural latex leather formula and a preparation process thereof to solve the above problems.
[0005] The technical solution of the present invention is achieved as follows: a natural latex leather, the leather is composed of a first layer, a second layer and a third layer in sequence;
[0006] The first layer of coating is made of the following raw materials in parts by weight: 100 parts of natural latex, 4-5 parts of sulfur powder, 1-1.5 parts of vulcanization aid, 0.8-1.2 parts of thickener, 2-4 parts of zinc oxide, 0.8-1.2 parts of antioxidant, and 0.8-1.2 parts of color paste;
[0007] The coating of the second layer is prepared by the following raw materials in parts by weight: 100 parts of natural latex, 4-5 parts of sulfur powder, 1-1.5 parts of vulcanization aid, 0.8-1.2 parts of foaming agent, 4-6 parts of thickener, 2-4 parts of zinc oxide, 0.8-1.2 parts of antioxidant, 0.8-1.2 parts of color paste, and 0.01-100 parts of filler;
[0008] The coating of the third layer includes the following raw materials in parts by weight: 100 parts of natural latex, 20-100 parts of polyurethane (preferably 25-35 parts), 4-5 parts of sulfur powder, 1-1.5 parts of vulcanization aid, 0.8-1.2 parts of thickener, 2-4 parts of zinc oxide, 0.8-1.2 parts of antioxidant, 0.8-1.2 parts of color paste, 1.5-2.5 parts of peroxide, 2-4 parts of polyhydroxy reinforcing material, and 0.4-0.6 parts of silane coupling agent; the polyhydroxy reinforcing material is at least one of polyhydroxy graphene and polyhydroxy carbon nanotube.
[0009] Furthermore, the coating of the first layer comprises the following raw materials in parts by weight: 100 parts of natural rubber latex, 4 parts of sulfur powder; 1.5 parts of vulcanizing aid, 1 part of thickener, 3 parts of zinc oxide, 1 part of antioxidant, and 1 part of color paste; the coating of the second layer comprises the following raw materials in parts by weight: 100 parts of natural rubber latex, 4 parts of sulfur powder, 1.5 parts of vulcanizing aid, 1 part of foaming agent, 5 parts of thickener, 3 parts of zinc oxide, 1 part of antioxidant, 1 part of color paste, and 1 part of filler; the coating of the third layer comprises the following raw materials in parts by weight: 100 parts of natural rubber latex, 30 parts of polyurethane, 4 parts of sulfur powder; 1.5 parts of vulcanizing aid, 1 part of thickener, 3 parts of zinc oxide, 1 part of antioxidant, 1 part of color paste, 2 parts of peroxide, 3 parts of polyhydroxy reinforcing material, and 0.5 part of silane coupling agent.
[0010] Furthermore, the total solid content of the natural latex is 60-65%, and the ammonia content is ≤0.15%.
[0011] Furthermore, the peroxide is composed of diisopropylbenzene peroxide and 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane in a mass ratio of 10:0.8-1.2.
[0012] Furthermore, the polyhydroxy reinforcing material is composed of polyhydroxy graphene and polyhydroxy carbon nanotubes in a mass ratio of 1.5-2.5:0.8-1.2.
[0013] Furthermore, the sulfur powder has a mesh size of 80 to 120.
[0014] Further, the vulcanization aid is composed of a thiuram vulcanization accelerator, a dithiocarbamate vulcanization accelerator and a xanthate vulcanization accelerator in a mass ratio of 0.8-1.2:1.8-2.2:0.8-1.2. Further, the thiuram vulcanization accelerator is a vulcanization accelerator TMTD, the dithiocarbamate vulcanization accelerator is a vulcanization accelerator ZDMC, and the xanthate vulcanization accelerator is a vulcanization accelerator ZBX.
[0015] Furthermore, the zinc oxide is composed of 30nm zinc oxide: 80nm zinc oxide in a mass ratio of 3.5-4.5:0.8-1.2.
[0016] Furthermore, the thickener is composed of sodium carboxymethyl cellulose and casein in a mass ratio of 0.8-1.2:2.4-2.6.
[0017] Furthermore, the antioxidant is composed of octylated diphenylamine and 2,2,4-trimethyl-1,2-dihydroquinoline in a mass ratio of 1:2.5-3.5.
[0018] Furthermore, the filler is composed of double fly ash, white carbon black and kaolin in a mass ratio of 0.8-1.2:2.5-3.5:0.8-1.2.
[0019] Furthermore, the foaming agent is composed of sodium lauryl sulfate, potassium oleate and sodium alkylbenzene sulfonate in a mass ratio of 0.8-1.2:0.8-1.2:0.8-1.2.
[0020] The preparation process of the natural latex leather comprises the following steps:
[0021] (1) Applying the first layer of coating on the base layer, and then vulcanizing it after coating;
[0022] (2) Applying a second layer of coating on the basis of the first layer, and then vulcanizing after the coating is completed;
[0023] (3) applying a third layer of coating after the vulcanization is completed, and then vulcanizing the coating; separating the base layer after the vulcanization to obtain natural latex leather;
[0024] The vulcanization is gradient temperature vulcanization, the gradient temperature range is 65° C. to 155° C., and the total vulcanization time is 4 to 12 minutes.
[0025] Furthermore, the coating thickness of the first layer of coating and the third layer of coating are both 8-12 microns; the coating thickness of the second layer of coating is 35-50 microns.
[0026] Furthermore, in step (1), the gradient temperature vulcanization procedure is: vulcanization at 65-75°C for 1-3 minutes, vulcanization at 85-95°C for 1-3 minutes, vulcanization at 105-115°C for 1-3 minutes, and vulcanization at 125-135°C for 1-3 minutes;
[0027] Step (2), the gradient temperature vulcanization procedure: 75-85° C. vulcanization for 1-3 minutes, 95-105° C. vulcanization for 1-3 minutes, 115-125° C. vulcanization for 1-3 minutes, and 135-145° C. vulcanization for 1-3 minutes;
[0028] Step (3), the procedure of the gradient temperature vulcanization is: vulcanization at 85-95°C for 1-3 minutes, vulcanization at 105-115°C for 1-3 minutes, vulcanization at 125-135°C for 1-3 minutes, and vulcanization at 145-155°C for 1-3 minutes.
[0029] Furthermore, in step (1), the gradient temperature vulcanization procedure is: 70° C. vulcanization for 2 minutes, 90° C. vulcanization for 2 minutes, 110° C. vulcanization for 2 minutes, and 130° C. vulcanization for 2 minutes;
[0030] Step (2), the gradient temperature vulcanization procedure: 80°C vulcanization for 2 minutes, 100°C vulcanization for 2 minutes, 120°C vulcanization for 2 minutes, and 140°C vulcanization for 2 minutes;
[0031] Step (3), the gradient temperature vulcanization procedure is: 90°C vulcanization for 2 minutes, 110°C vulcanization for 2 minutes, 130°C vulcanization for 2 minutes, and 150°C vulcanization for 2 minutes.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) The natural latex leather prepared by the formula and process of the present invention not only has good performance, but also further improves the safety and environmental protection of the leather, effectively promoting the development of the natural rubber industry.
[0034] (2) The present invention uses natural latex as raw material and adopts the formula and process of the present invention to make leather. The leather has good performance indicators such as tensile strength, elongation, leather tear strength, UV resistance, wear resistance, air permeability, and waterproofness. In addition, the surface transfer pattern is clear and the imitation leather effect is good.
[0035] (3) The present invention uses natural latex as the main raw material, adopts diisopropylbenzene peroxide and 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, combines polyhydroxy graphene and polyhydroxy carbon nanotubes, and adds a silane coupling agent to promote the occurrence of a cross-linking reaction; this composite system can form a network structure in the leather, enhance its support and overall strength, and effectively improve the mechanical properties and stability of the material. At the same time, the water resistance, wear resistance, toughness, tensile strength and adhesion of the leather are significantly improved, and the weather resistance and antioxidant capacity of the product are also improved, achieving a dual improvement in functionality and durability, and comprehensively improving the overall performance of the leather and extending its service life.
[0036] (4) The specially formulated coating of the present invention adopts a specific gradient temperature vulcanization procedure, and gradually controls and adjusts the temperature change during the vulcanization process to achieve optimized chemical reactions and material structures, thereby significantly improving the performance of leather. DETAILED DESCRIPTION
[0037] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.
[0038] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0039] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0040] Example 1
[0041] (I) Leather formula
[0042] A natural latex leather, which is composed of a first layer, a second layer and a third layer in sequence; the coating formula is shown in the following table:
[0043] Table 1: First layer coating formula
[0044] Serial number Components Dosage(g) 1 Natural latex 100 2 Sulfur powder 4.0 3 Vulcanization accelerator 1.5 4 Thickener 1.0 5 Zinc Oxide 3.0 6 Antioxidant 1.0 7 Color paste 1.0
[0045]
[0046] Serial number Components Dosage(g) 1 Natural latex 100 2 Sulfur powder 4.0 3 Vulcanization accelerator 1.5 4 Foaming agent 1.0 5 Thickener 5.0 6 Zinc Oxide 3.0 7 Antioxidant 1.0 8 Color paste 1.0 9 filler 1.0
[0047] Table 3 Coating formula for the third layer
[0048] Serial number Components Dosage(g) 1 Natural latex 100 2 Polyurethane 30 3 Sulfur powder 4.0 4 Vulcanization accelerator 1.5 5 Thickener 1.0 6 Zinc Oxide 3.0 7 Antioxidant 1.0 8 Color paste 1.0 9 peroxide 2.0 10 Polyhydroxy reinforcement material 3.0 11 Silane coupling agent 0.5
[0049] In Table 1-3, natural rubber latex: total solid content is 60-65%, ammonia content is 0.1%-0.15%;
[0050] Sulfur powder: 100 mesh;
[0051] Vulcanization accelerator: composed of a thiuram vulcanization accelerator, a dithiocarbamate vulcanization accelerator and a xanthate vulcanization accelerator in a mass ratio of 1:2:1; the thiuram vulcanization accelerator is a vulcanization accelerator TMTD, the dithiocarbamate vulcanization accelerator is a vulcanization accelerator ZDMC, and the xanthate vulcanization accelerator is a vulcanization accelerator ZBX;
[0052] Foaming agent: composed of sodium lauryl sulfate, potassium oleate and sodium alkylbenzene sulfonate in a mass ratio of 1:1:1;
[0053] Thickener: composed of sodium carboxymethyl cellulose and casein in a mass ratio of 1:5;
[0054] Zinc oxide: composed of 30nm zinc oxide: 80nm zinc oxide in a mass ratio of 4:1;
[0055] Antiaging agent: It is composed of octylated diphenylamine and 2,2,4-trimethyl-1,2-dihydroquinoline in a mass ratio of 1:3.
[0056] Filler: double fly ash, white carbon black and kaolin in a mass ratio of 1:3:1;
[0057] Peroxide: composed of diisopropylbenzene peroxide and 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane in a mass ratio of 10:1;
[0058] The polyhydroxy reinforcement material is composed of polyhydroxy graphene and polyhydroxy carbon nanotubes in a mass ratio of 2:1;
[0059] Silane coupling agent: silane coupling agent kh-560;
[0060] Polyurethane: water-based polyurethane emulsion, purchased from Guangzhou Shanghe New Material Technology Co., Ltd., model WPU-3015.
[0061] (ii) Leather craft
[0062] (1) coating the first layer of coating on the release paper with a coating thickness of about 10 filaments. After coating, gradient temperature vulcanization is performed;
[0063] Table 4 First layer gradient temperature vulcanization schedule
[0064] Serial number Vulcanization temperature Vulcanization time 1 70℃ 2 minutes 2 90℃ 2 minutes 3 110℃ 2 minutes 4 130℃ 2 minutes
[0065] (2) Apply a second layer of coating on the basis of the first layer, with a coating thickness of about 45 μm. After the coating is completed, gradient temperature vulcanization is performed;
[0066] Table 5 Second layer gradient temperature vulcanization schedule
[0067] Serial number Vulcanization temperature Vulcanization time 1 80℃ 2 minutes 2 100℃ 2 minutes 3 120℃ 2 minutes 4 140℃ 2 minutes
[0068] (3) After the vulcanization is completed, the third layer of coating is applied with a coating thickness of about 10 silks. After the coating is completed, gradient temperature vulcanization is carried out.
[0069] The above vulcanization is carried out using a gradient temperature vulcanization program. The gradient temperature vulcanization program is shown in Table 4:
[0070] Table 6 Third layer gradient temperature vulcanization schedule
[0071] Serial number Vulcanization temperature Vulcanization time 1 90℃ 2 minutes 2 110℃ 2 minutes 3 130℃ 2 minutes 4 150℃ 2 minutes
[0072] After the vulcanization is completed, the release paper is separated to obtain the natural rubber latex for leather making.
[0073] Example 2
[0074] (I) Leather formula
[0075] A natural latex leather, which is composed of a first layer, a second layer and a third layer in sequence; the coating formula is shown in the following table:
[0076] Table 7 Coating formula for the first layer
[0077] Serial number Components Dosage(g) 1 Natural latex 100 2 Sulfur powder 4.5 3 Vulcanization accelerator 1.0 4 Thickener 0.8 5 Zinc Oxide 3.9 6 Antioxidant 0.8 7 Color paste 1.0
[0078] Table 8 Coating formula for the second layer
[0079]
[0080]
[0081] Table 9 Coating formula for the third layer
[0082] Serial number Components Dosage(g) 1 Natural latex 100 2 Polyurethane 30 3 Sulfur powder 4.5 4 Vulcanization accelerator 1.0 5 Thickener 0.8 6 Zinc Oxide 3.9 7 Antioxidant 0.8 8 Color paste 1.0 9 peroxide 1.5 10 Polyhydroxy reinforcement material 2.5 11 Silane coupling agent 0.6
[0083] In Tables 7-9, natural rubber latex: total solid content is 60-65%, ammonia content is 0.1%-0.15%;
[0084] Sulfur powder: 100 mesh;
[0085] Vulcanization accelerator: composed of a thiuram vulcanization accelerator, a dithiocarbamate vulcanization accelerator and a xanthate vulcanization accelerator in a mass ratio of 1:2:1; the thiuram vulcanization accelerator is a vulcanization accelerator TMTD, the dithiocarbamate vulcanization accelerator is a vulcanization accelerator ZDMC, and the xanthate vulcanization accelerator is a vulcanization accelerator ZBX;
[0086] Foaming agent: composed of sodium lauryl sulfate, potassium oleate and sodium alkylbenzene sulfonate in a mass ratio of 1:1:1;
[0087] Thickener: composed of sodium carboxymethyl cellulose and casein in a mass ratio of 1:5;
[0088] Zinc oxide: composed of 30nm zinc oxide: 80nm zinc oxide in a mass ratio of 4:1;
[0089] Antiaging agent: It is composed of octylated diphenylamine and 2,2,4-trimethyl-1,2-dihydroquinoline in a mass ratio of 1:3.
[0090] Filler: double fly ash, white carbon black and kaolin in a mass ratio of 1:3:1;
[0091] Peroxide: composed of diisopropylbenzene peroxide and 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane in a mass ratio of 10:1;
[0092] The polyhydroxy reinforcing material is composed of polyhydroxy graphene and polyhydroxy carbon nanotubes in a mass ratio of 2:1.
[0093] Silane coupling agent: silane coupling agent kh-560;
[0094] Polyurethane: water-based polyurethane emulsion, purchased from Guangzhou Shanghe New Material Technology Co., Ltd., model WPU-3015.
[0095] (ii) Leather craft
[0096] The leather process of this embodiment is consistent with that of embodiment 1.
[0097] Example 3
[0098] (I) Leather formula
[0099] A natural latex leather, which is composed of a first layer, a second layer and a third layer in sequence; the coating formula is shown in the following table:
[0100] Table 10 Coating formula for the first layer
[0101] Serial number Components Dosage(g) 1 Natural latex 100 2 Sulfur powder 5.0 3 Vulcanization accelerator 1.0 4 Thickener 1.2 5 Zinc Oxide 2.3 6 Antioxidant 1.2 7 Color paste 0.8
[0102] Table 11 Coating formula for the second layer
[0103]
[0104]
[0105] Table 12 Coating formula for the third layer
[0106] Serial number Components Dosage(g) 1 Natural latex 100 2 Polyurethane 30 3 Sulfur powder 5.0 4 Vulcanization accelerator 1.0 5 Thickener 1.2 6 Zinc Oxide 2.3 7 Antioxidant 1.2 8 Color paste 0.8 9 peroxide 2.5 10 Polyhydroxy reinforcement material 4.0 11 Silane coupling agent 0.4
[0107] In Tables 10-12, natural rubber latex: total solid content is 60-65%, ammonia content is 0.1%-0.15%;
[0108] Sulfur powder: 100 mesh;
[0109] Vulcanization accelerator: composed of a thiuram vulcanization accelerator, a dithiocarbamate vulcanization accelerator and a xanthate vulcanization accelerator in a mass ratio of 1:2:1; the thiuram vulcanization accelerator is a vulcanization accelerator TMTD, the dithiocarbamate vulcanization accelerator is a vulcanization accelerator ZDMC, and the xanthate vulcanization accelerator is a vulcanization accelerator ZBX;
[0110] Foaming agent: composed of sodium lauryl sulfate, potassium oleate and sodium alkylbenzene sulfonate in a mass ratio of 1:1:1;
[0111] Thickener: composed of sodium carboxymethyl cellulose and casein in a mass ratio of 1:5;
[0112] Zinc oxide: composed of 30nm zinc oxide: 80nm zinc oxide in a mass ratio of 4:1;
[0113] Antiaging agent: It is composed of octylated diphenylamine and 2,2,4-trimethyl-1,2-dihydroquinoline in a mass ratio of 1:3.
[0114] Filler: double fly ash, white carbon black and kaolin in a mass ratio of 1:3:1;
[0115] Peroxide: composed of diisopropylbenzene peroxide and 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane in a mass ratio of 10:1;
[0116] The polyhydroxy reinforcement material is composed of polyhydroxy graphene and polyhydroxy carbon nanotubes in a mass ratio of 2:1;
[0117] Silane coupling agent: silane coupling agent kh-560;
[0118] Polyurethane: water-based polyurethane emulsion, purchased from Guangzhou Shanghe New Material Technology Co., Ltd., model WPU-3015.
[0119] (ii) Leather craft
[0120] The leather process of this embodiment is consistent with that of embodiment 1.
[0121] Comparative Example 1
[0122] The main difference from Example 1 is that the polyhydroxy reinforcing material is replaced by an equal amount of nano-silicon dioxide, and the other operations are consistent with Example 1.
[0123] Comparative Example 2
[0124] The main difference from Example 1 is that the peroxide is replaced by an equal amount of dicumyl peroxide, and the other operations are consistent with Example 1.
[0125] Comparative Example 3
[0126] (i) The leather formula is the same as in Example 1.
[0127] (II) The main difference between the leather process and Example 1 is that the temperature of the gradient temperature vulcanization program is different. The three layers are all processed according to the gradient temperature vulcanization program in the following table.
[0128] Table 13 Gradient temperature vulcanization schedule
[0129] Serial number Vulcanization temperature Vulcanization time 1 70℃ 2 minutes 2 110℃ 2 minutes 3 130℃ 2 minutes 4 150℃ 2 minutes
[0130] The other processes are consistent with those in Example 1.
[0131] Comparative Example 4
[0132] The main difference from Example 1 is that all the polyhydroxy reinforcing materials use polyhydroxy graphene, that is, no polyhydroxy carbon nanotubes are added, and other operations are consistent with Example 1.
[0133] Comparative Example 5
[0134] The main difference from Example 1 is that the vulcanization accelerator TMTD is used as the vulcanization aid. Other operations are the same as those in Example 1.
[0135] Comparative Example 6
[0136] The main difference from Example 1 is that all zinc oxide uses 30nm zinc oxide, that is, there is no 80nm zinc oxide. Other operations are consistent with Example 1.
[0137] Comparative Example 7
[0138] The main difference from Example 1 is that all thickeners are sodium carboxymethyl cellulose. Other operations are consistent with Example 1.
[0139] Comparison Example
[0140] The difference from Example 1 is that the natural latex in the coating formula of each layer is replaced by water-based polyurethane emulsion (model WPU-3015, purchased from Guangzhou Shanghe New Material Technology Co., Ltd.) The other process operations are consistent with Example 1.
[0141] Test example
[0142] The products prepared in Examples 1 to 3 and Comparative Examples 1 to 7 were tested, and the results are shown in the following table, and compared with the polyurethane leather of the control example:
[0143] (1) Tensile strength (radial): ISO 3376;
[0144] (2) Elongation (weft): ISO 3376;
[0145] (3) Leather tear strength: ISO 3377-1;
[0146] (4) Color fastness to light: ISO 105-B02;
[0147] (5) Color fastness to rubbing (dry staining / wet staining): ISO 105-X12;
[0148] (6) Water splash test: ISO 4920;
[0149] The test results are shown in Tables 14 to 15.
[0150] Table 14
[0151]
[0152] Table 15
[0153]
[0154] The above results show that the performance of the natural latex leather prepared by the process of Examples 1 to 3 of the present invention is significantly better than that of the control example (polyurethane leather).
[0155] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A natural latex leather, characterized in that: The leather is composed of a first layer, a second layer and a third layer in sequence; The first layer of coating is made of the following raw materials in parts by weight: 100 parts of natural latex, 4-5 parts of sulfur powder, 1-1.5 parts of vulcanization aid, 0.8-1.2 parts of thickener, 2-4 parts of zinc oxide, 0.8-1.2 parts of antioxidant, and 0.8-1.2 parts of color paste; The coating of the second layer is prepared by the following raw materials in parts by weight: 100 parts of natural latex, 4-5 parts of sulfur powder, 1-1.5 parts of vulcanization aid, 0.8-1.2 parts of foaming agent, 4-6 parts of thickener, 2-4 parts of zinc oxide, 0.8-1.2 parts of antioxidant, 0.8-1.2 parts of color paste, and 0.01-100 parts of filler; The coating of the third layer includes the following raw materials in parts by weight: 100 parts of natural latex, 20-100 parts of polyurethane, 4-5 parts of sulfur powder, 1-1.5 parts of vulcanization aid, 0.8-1.2 parts of thickener, 2-4 parts of zinc oxide, 0.8-1.2 parts of antioxidant, 0.8-1.2 parts of color paste, 1.5-2.5 parts of peroxide, 2-4 parts of polyhydroxy reinforcing material, and 0.4-0.6 parts of silane coupling agent; the polyhydroxy reinforcing material is at least one of polyhydroxy graphene and polyhydroxy carbon nanotube.
2. The natural latex leather according to claim 1, characterized in that The coating of the first layer comprises the following raw materials in parts by weight: 100 parts of natural rubber latex, 4 parts of sulfur powder; 1.5 parts of vulcanizing aid, 1 part of thickener, 3 parts of zinc oxide, 1 part of antioxidant, and 1 part of color paste; the coating of the second layer comprises the following raw materials in parts by weight: 100 parts of natural rubber latex, 4 parts of sulfur powder, 1.5 parts of vulcanizing aid, 1 part of foaming agent, 5 parts of thickener, 3 parts of zinc oxide, 1 part of antioxidant, 1 part of color paste, and 1 part of filler; the coating of the third layer comprises the following raw materials in parts by weight: 100 parts of natural rubber latex, 30 parts of polyurethane, 4 parts of sulfur powder; 1.5 parts of vulcanizing aid, 1 part of thickener, 3 parts of zinc oxide, 1 part of antioxidant, 1 part of color paste, 2 parts of peroxide, 3 parts of polyhydroxy reinforcing material, and 0.5 part of silane coupling agent.
3. The natural latex leather according to claim 1, characterized in that The peroxide is composed of diisopropylbenzene peroxide and 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane in a mass ratio of 10:0.8-1.
2.
4. The natural latex leather according to claim 1, characterized in that The polyhydroxy reinforcing material is composed of polyhydroxy graphene and polyhydroxy carbon nanotubes in a mass ratio of 1.5-2.5:0.8-1.
2.
5. The natural latex leather according to claim 1, characterized in that The total solid content of the natural latex is 60-65%, and the ammonia content is ≤0.15%.
6. The natural latex leather according to claim 1, characterized in that The sulfur powder has a mesh size of 80 to 120; the vulcanization aid is composed of a thiuram vulcanization accelerator, a dithiocarbamate vulcanization accelerator and a xanthate vulcanization accelerator in a mass ratio of 0.8 to 1.2:1.8 to 2.2:0.8 to 1.2, wherein the thiuram vulcanization accelerator is a vulcanization accelerator TMTD, the dithiocarbamate vulcanization accelerator is a vulcanization accelerator ZDMC, and the xanthate vulcanization accelerator is a vulcanization accelerator ZBX; The zinc oxide is composed of 30nm zinc oxide: 80nm zinc oxide in a mass ratio of 3.5-4.5:0.8-1.2; the thickener is composed of sodium carboxymethyl cellulose and casein in a mass ratio of 0.8-1.2:2.4-2.6; The antioxidant is composed of octylated diphenylamine and 2,2,4-trimethyl-1,2-dihydroquinoline in a mass ratio of 1:2.5-3.5; The filler is composed of double fly ash, white carbon black and kaolin in a mass ratio of 0.8-1.2:2.5-3.5:0.8-1.2; the foaming agent is composed of sodium lauryl sulfate, potassium oleate and sodium alkylbenzene sulfonate in a mass ratio of 0.8-1.2:0.8-1.2:0.8-1.
2.
7. The process for preparing the natural latex leather according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Applying the first layer of coating on the base layer, and then vulcanizing it after coating; (2) Applying a second layer of coating on the basis of the first layer, and then vulcanizing after the coating is completed; (3) applying a third layer of coating after the vulcanization is completed, and then vulcanizing the coating; separating the base layer after the vulcanization to obtain natural latex leather; The vulcanization is gradient temperature vulcanization, the gradient temperature range is 65° C. to 155° C., and the total vulcanization time is 4 to 12 minutes.
8. The process for preparing natural latex leather according to claim 1, characterized in that: The coating thickness of the first layer of coating and the third layer of coating are both 8-12 microns; the coating thickness of the second layer of coating is 35-50 microns.
9. The process for preparing natural latex leather according to claim 1, characterized in that: Step (1), the gradient temperature vulcanization procedure: 65-75° C. vulcanization for 1-3 minutes, 85-95° C. vulcanization for 1-3 minutes, 105-115° C. vulcanization for 1-3 minutes, and 125-135° C. vulcanization for 1-3 minutes; Step (2), the gradient temperature vulcanization procedure: 75-85° C. vulcanization for 1-3 minutes, 95-105° C. vulcanization for 1-3 minutes, 115-125° C. vulcanization for 1-3 minutes, and 135-145° C. vulcanization for 1-3 minutes; Step (3), the procedure of the gradient temperature vulcanization is: vulcanization at 85-95°C for 1-3 minutes, vulcanization at 105-115°C for 1-3 minutes, vulcanization at 125-135°C for 1-3 minutes, and vulcanization at 145-155°C for 1-3 minutes.
10. The process for preparing natural latex leather according to claim 1, characterized in that: Step (1), the gradient temperature vulcanization procedure: 70°C vulcanization for 2 minutes, 90°C vulcanization for 2 minutes, 110°C vulcanization for 2 minutes, and 130°C vulcanization for 2 minutes; Step (2), the gradient temperature vulcanization procedure: 80°C vulcanization for 2 minutes, 100°C vulcanization for 2 minutes, 120°C vulcanization for 2 minutes, and 140°C vulcanization for 2 minutes; Step (3), the gradient temperature vulcanization procedure is: 90°C vulcanization for 2 minutes, 110°C vulcanization for 2 minutes, 130°C vulcanization for 2 minutes, and 150°C vulcanization for 2 minutes.
